Video game spaces image, play, and structure in 3D game worlds - Nitsche, Michael, 1968- (MIT Press, 2008)
Here, Nitsche introduces five analytical layers - rule-based space, mediated space, fictional space, play space, and social space - and uses them in the analyses of games that range from early classics to recent titles.
Keywords: Video games.; elektronické knihy; electronic books